Modeling the Competitive Advantage of Companies within the Hotel Industry in a Region - Yurievna Nikolskaya, Elena; Vladimirovna Pasko, Olga; Anatol'evna Volkova, Inna; Nikolaevna Anikina, Elena; Yevgenievna Lebedeva, Olga (International Journal of Engineering and Technology, 2018)
This paper focuses on the development of techniques for modeling the competitive advantage of companies within the hotel industry in a region. The authors make the case that their proposed techniques for modeling the competitive advantage of companies within the hotel industry in a region can help to cumulatively evaluate and give a well-substantiated quantitative and qualitative assessment of the sector’s competitiveness factoring in a set of specific indicators. This kind of algorithm for constructing a model for competitive advantage could help assess in real time the quality of services provided within the hospitality sphere and conduct comparative analyses across the nation’s regions.